2014
DOI: 10.1088/0953-4075/47/11/115302
|View full text |Cite
|
Sign up to set email alerts
|

Zero-momentum coupling induced transitions of ground states in Rashba spin–orbit coupled Bose–Einstein condensates

Abstract: We investigate the transitions of ground states induced by zero momentum (ZM) coupling in pseudospin-1/2 Rashba spin-orbit coupled Bose-Einstein condensates confined in a harmonic trap. In a weak harmonic trap, the condensate presents a plane wave (PW) state, a stripe state or a spin polarized ZM state, and the particle distribution of the stripe state is weighted equally at two points in the momentum space without ZM coupling. The presence of ZM coupling induces an imbalanced particle distribution in the mome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 40 publications
2
29
0
Order By: Relevance
“…In Ref. [49], transitions of ground states, induced by the zero-momentum coupling in the Rashba-SO-coupled BEC with pseudospin 1/2, were investigated in the presence of the confining HO potential. Fragmentation of SO-coupled spinor BEC was studied in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. [49], transitions of ground states, induced by the zero-momentum coupling in the Rashba-SO-coupled BEC with pseudospin 1/2, were investigated in the presence of the confining HO potential. Fragmentation of SO-coupled spinor BEC was studied in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…We consider a pseudospin-1/2 Bose-Einstein condensates, with Rashba spin-orbit and Rabi couplings trapped under a harmonic potential with strong axial confinement. The properties of such a SO coupled BECs can be described by a set of coupled Gross-Pitaevskii (GP) equations in dimensionless form as [29,33]:…”
Section: Mean-field Model and Numerical Simulation Detailsmentioning
confidence: 99%
“…However, under the influence of a strong harmonic trap with zero Rabi coupling vortex pairs can be formed for each component, which gets organized on honeycomb vortex-antivortex (VA) lattice. This configuration leads to three kinds of spin textures: up HQV, down HQV and spin-2 textures [33]. Sinha et al showed that interplay between the SO coupling and mean-field nonlinearity in trapped 2D SO coupled BECs leads to the formation of vortex lattice and vortex stripe configuration even in the absence of external angular momentum [34].…”
Section: Introductionmentioning
confidence: 99%
“…It is straightforward to note that the energy spectrum is a simple free-particle parabolic dispersion, indicating the existence of non-degenerate single-point lowest energy ground state. Figure 1(b) is the case with only Rashba SO coupling and the single-particle energy spectrum consists of ring of infinitely degenerate lowest energy states in momentum space, which is typically identified as Rashba ring [24,31,32].…”
Section: The Model Equationmentioning
confidence: 99%
“…The particular feature of the Rashba type SO coupling is the existence of infinite degeneracy in the minima of single particle energy spectrum in the momentum space [24,31,32]. The system also admits two kinds of phases namely, the plane wave (PW) phase and the stripe wave phase (SW) as a consequence of the competition between the inter-and intra-component interaction.…”
Section: Introductionmentioning
confidence: 99%